Preoperative Plasma Fibrinogen Level as a Significant Prognostic Factor in Patients With Localized Renal Cell Carcinoma After Surgical Treatment. Issue 4 (January 2016) - Lee, Hakmin; Lee, Sang Eun; Byun, Seok-Soo; Kim, Hyeon Hoe; Kwak, Cheol; Hong, Sung Kyu
Abstract : Abstract: We sought to investigate the association of preoperative fibrinogen levels with clinicopathologic outcomes after surgical treatment of nonmetastatic renal cell carcinoma. We reviewed the records of 1511 patients who had their fibrinogen levels measured preceding surgery. The associations between preoperative fibrinogen level and risk of adverse clinicopathologic outcomes were tested using the multivariate logistic regression and multiple Cox-proportional hazards model, respectively. Based on plasma fibrinogen levels, we stratified the patients into 2 groups with a cut-off value of 328 mg/dL. Kaplan–Meier analysis showed significantly inferior survival outcomes in progression-free ( P  < 0.001), cancer-specific ( P  < 0.001), and overall survival ( P  < 0.001). In multivariate analyses, a high fibrinogen level (≥328 mg/dL) was significantly related to a higher Fuhrman grade (hazard ratio [HR] 1.374, P  = 0.006) and a larger tumor size (≥7 cm) (HR 2.364, P  < 0.001). Multivariate Cox analysis also revealed that a high preoperative fibrinogen level is a significant predictor for poor disease progression (HR 1.857, P  < 0.001), cancer-specific survival (HR 3.608, P  = 0.003), and overall survival (HR 1.647, P  = 0.027). Increased plasma fibrinogen levels were significantly associated with poor pathological features and worse survival outcomes in patients with nonmetastatic renal cell carcinoma after surgical treatment. Further evaluations such as prospective randomized trials are needed to understand the underlying mechanism for these associations.